Association of prenatal alcohol exposure and prenatal maternal depression with offspring low-grade inflammation in early adolescence - Maschke, Janina; Roetner, Jakob; Bösl, Sophia; Plank, Anne-Christine; Rohleder, Nicolas; Goecke, Tamme W.; Fasching, Peter; Beckmann, Matthias; Kratz, Oliver; Moll, Gunther; Lenz, Bernd; Kornhuber, Johannes; et al. (International Journal of Environmental Research and Public Health, 2021)
(1) This longitudinal study aimed to investigate the link between prenatal alcohol exposure and prenatal maternal depression with the offspring’s low-grade inflammatory status. (2) Prenatal alcohol exposure was determined via maternal self-report during the 3rd trimester of pregnancy (self-report+: n = 29) and the meconium alcohol metabolite Ethyl Glucuronide (EtG), collected at birth (≥30 ng/g: n = 23). The Edinburgh Postnatal Depression Scale (EPDS) was used to screen for prenatal maternal depressive symptoms during the 3rd trimester (≥10: n = 35). Fifteen years later, 122 adolescents (M = 13.32 years; 48.4% female) provided blood samples for the analysis of high sensitivity C-reactive protein (hsCRP; M = 0.91; SD = 1.28). (3) Higher hsCRP levels were found in EtG positive adolescents (p = 0.036, ηp2 = 0.04) and an inverse non-significant dose–response relation with hsCRP (r = −0.35, p = 0.113). For maternal self-reported prenatal alcohol consumption (p = 0.780, ηp2 = 0.00) and prenatal depressive symptoms (p = 0.360, ηp2 = 0.01) no differences for hsCRP levels between the affected and unaffected groups were found. (4) Adolescents with prenatal alcohol exposure are at risk for low-grade systemic inflammation. The EtG biomarker may be more accurate compared to self-reports. The findings suggest that prenatal maternal depression does not evoke low-grade systemic inflammation.
CRIS-Team Scopus Importer:2021-08-06
Keywords: Early adolescence; High-sensitivity C-reactive protein (hsCRP); Low-grade systemic inflammation; Maternal self-report; Meconium ethyl glucuronide (EtG); Pregnancy; Prenatal alcohol exposure (PAE); Prenatal depression

Effects of prenatal alcohol exposition on cognitive outcomes in childhood and youth: a longitudinal analysis based on meconium ethyl glucuronide. - Roetner, Jakob; Van Doren, Jessica; Maschke, Janina; Kulke, Louisa; Pontones, Constanza; Fasching, Peter A.; Beckmann, Matthias W.; Lenz, Bernd; Kratz, Oliver; Moll, Gunther; Kornhuber, Johannes; Eichler, Anna (European archives of psychiatry and clinical neuroscience, 2024)
BACKGROUND: Prenatal alcohol exposure (PAE) has been linked to severe, adverse child outcomes. However, little is known regarding subclinical outcomes of low/moderate PAE and its longitudinal consequences, especially regarding neurophysiological and neurocognitive development. A newborn biomarker of PAE, meconium ethyl glucuronide (EtG), has been shown to predict cognitive impairments in primary-school-aged children. The current study investigated the ongoing effects of subclinical PAE in adolescence. METHODS: A sample of n = 96 mother-child dyads of the FRAMES/FRANCES cohort were classified into PAE/no PAE using EtG with a 10 ng/g cutoff. Mothers were recruited during pregnancy and children were assessed during primary-school age (M = 7.57, SD = 0.65, range: 6.00-9.92 years) and adolescence (M = 13.26, SD = 0.31, range: 12.79-14.20 years) on three levels: clinical (ADHD rating), neuropsychological (IQ score and performance in a go/nogo task), and neurophysiological (analysis of P3 event-related potentials (ERP) during said go/nogo task). Developmental outcomes and courses following PAE were assessed using rmANCOVAs, controlling for relevant confounders (socioeconomic status (SES), birth weight, and maternal psychopathology). RESULTS: Neurophysiological impairments emerged for exposed children in the form of diminished attentional resource recruiting in childhood and adolescence (reduced go-P3 amplitudes) with no differences in performance. Neuropsychological testing showed a reduced IQ score for both time points with dose-dependent effects in childhood. Clinical ADHD symptoms were not significantly affected. CONCLUSION: Subclinical PAE, as determined by meconium EtG, has negative developmental consequences on cognitive function that persist from childhood to adolescence. These findings suggest that there is no safe limit for alcohol consumption during pregnancy and that more thorough screening of alcohol consumption during pregnancy is necessary for early identification and treatment of at-risk children.
EVALuna2:538816

Genome-Wide DNA Methylation Patterns in Children Exposed to Nonpharmacologically Treated Prenatal Depressive Symptoms: Results From 2 Independent Cohorts - Stonawski, Valeska; Roetner, Jakob; Goecke, Tamme W.; Fasching, Peter; Beckmann, Matthias; Kornhuber, Johannes; Kratz, Oliver; Moll, Gunther; Eichler, Anna; Heinrich, Hartmut; Frey, Stefan (Epigenetics Insights, 2020)
Background: Maternal depressive symptoms are a common phenomenon during pregnancy and are related to negative outcomes for child development and health. Modifications in child DNA methylation are discussed as an underlying mechanism for the association between prenatal depressive symptoms and alterations in child outcomes. However, formerly reported genome-wide associations have yet to be replicated. Methods: In an epigenome-wide association study (EWAS), alterations of DNA methylation related to maternal prenatal depressive symptoms were investigated in buccal cell samples from 174 children (n = 52 exposed to prenatal depressive symptoms; 6-9 years old) of the German longitudinal study FRAMES-FRANCES. Whole blood samples from the independent, age-comparable ARIES subsample of the ARIES/ALSPAC study (n = 641; n = 159 exposed to prenatal depressive symptoms; 7-8 years old) were examined as a confirmation sample. Depressive symptoms were assessed with the Edinburgh Postnatal Depression Scale. DNA methylation was analyzed with the Infinium Human Methylation 450k BeadChip. Modifications in single CpGs, regions, and biological pathways were investigated. Results were adjusted for age and birth outcomes as well as postnatal and current maternal depressive symptoms. Analyses were performed for the whole sample as well as separated for sex. Results: The EWAS yielded no differentially methylated CpG or region as well as no accordance between samples withstanding correction for multiple testing. In pathway analyses, no overlapping functional domain was found to be enriched for either sample. A comparison of current and former findings suggests some overlapping methylation modifications from infancy to childhood. Results suggest that there might be sex-specific differential methylation, which should be further investigated in additional studies. Conclusions: The current, mainly nonsignificant, results challenge the assumption of consistent modifications of DNA methylation in children exposed to prenatal depressive symptoms. Despite the relatively small sample size used in this study, this lack of significant results may reflect diverse issues of environmental epigenetic studies, which need to be addressed in future research.
CRIS-Team Scopus Importer:2020-06-26
Keywords: ALSPAC; ARIES; DNA methylation; epigenetics; FRANCES; Pregnancy; prenatal depression

Maternal depression and child development: A prospective analysis of consequences, risk and protective factors - Roetner, Jakob; Petry, Janna; Niekamp, Julia; Maschkel, Janina; Goecke, Tamme W.; Fasching, Peter; Beckmann, Matthias; Kornhuber, Johannes; Kratz, Oliver; Moll, Gunther; Eichler, Anna (Zeitschrift für Kinder- und Jugendpsychiatrie und Psychotherapie, 2022)
Maternal depression and child development: A prospective analysis of consequences, risk and protective factors Abstract. Objective: Maternal stress, specifically maternal mental health problems, are considered risk factors for child development. The literature suggests that prenatal depressive symptoms as well as depressive symptoms are a widespread phenomenon during the further development of the child and have repeatedly been shown to have adverse effects on child mental health outcomes. The present study examined the longitudinal relationships between maternal depression (prenatal, postnatal, during childhood and adolescence) and child mental health from childhood to adolescence. Possible risk and protective factors were also considered. Method: N = 112 mothers were assessed for depressive symptoms via a questionnaire at four different timepoints (prenatal, T1; postnatal, T2; during childhood, T3; during adolescence, T4). Children's externalizing and internalizing symptoms (50.9 % girls) were assessed by their mothers both during childhood (M = 7.68, SD = 0.76 years) and during adolescence (M = 13.23, SD = 0.27 years). We evaluated the relationships between maternal depressive symptoms and children's externalizing/internalizing symptoms using multiple regression models and analyzed possible risk and protective factors using moderation analysis. Results: Externalizing/Internalizing symptoms were not directly associated with maternal depressive symptoms, while associations between such symptoms and maladaptive behavior were found in adolescents. The socioeconomic status of families showed a different risk profile for prenatal and postnatal depressive symptoms. The IQ of the children proved to be a risk factor for internalizing symptoms. Conclusions: Maternal depressive symptoms at any time during child development - in combination with further risk factors - have an impact on child mental health. The early identification of maternal symptoms followed by interventions to differentiate between prenatal and postnatal depression - especially in the context of socioeconomic status - are highly relevant for child development.
CRIS-Team WoS Importer:2022-04-08
Keywords: Pränatale Depressivität; kindliche Erlebens- und Verhaltensauffälligkeiten; Risiko- und Schutzfaktoren; sozioökonomischer Status; Intelligenzquotient; Prenatal depression; child behavior; risk and protective factors; socioeconomic status; intelligence quotient

Prenatal alcohol exposure and the facial phenotype in adolescents: A study based on meconium ethyl glucuronide - Maschke, Janina; Roetner, Jakob; Goecke, Tamme; Fasching, Peter; Beckmann, Matthias; Kratz, Oliver; Moll, Gunther; Lenz, Bernd; Kornhuber, Johannes; Eichler, Anna (Brain Sciences, 2021)
Here, we explore the effects of prenatal alcohol exposure (PAE) in adolescence. We investigated associations between meconium ethyl glucoronide (EtG) and facial malformation. For 29 children (66/63 male/female; M = 13.3, SD = 0.32, 12–14 years), PAE was implemented by newborn meconium EtG and maternal self-reports during the third trimester. Cognitive development was operationalized by standardized scores (WISC V). The EtG cut-off values were set at ≥10 ng/g (n = 32, 24.8% EtG10+) and ≥112 ng/g (n = 20, 15.5% EtG112+). The craniofacial shape was measured using FAS Facial Photographic Analysis Software. EtG10+− and EtG112+-affected children exhibited a shorter palpebral fissure length (p = 0.031/p = 0.055). Lip circularity was smaller in EtG112+-affected children (p = 0.026). Maternal self-reports were not associated (p > 0.164). Lip circularity correlated with fluid reasoning (EtG10+ p = 0.031; EtG112+ p = 0.298) and working memory (EtG10+ p = 0.084; EtG112+ p = 0.144). The present study demonstrates visible effects of the facial phenotype in exposed adolescents. Facial malformation was associated with a child’s cognitive performance in the alcohol-exposed group. The EtG biomarker was a better predictor than maternal self-reports.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Alcohol; Biomarker; Craniofacial shape; Ethyl glucuronide (EtG); Facial malformations; Inner canthal distance; Intrauterine alcohol exposure; Lip circularity; Meconium; Palpebral fissure length